PENGAWASAN DINAS KESEHATAN PEMERINTAH KOTA PEKANBARU TERHADAP KUALITAS AIR MINUM USAHA DEPOT AIR MINUM ISI ULANG BERDASARKAN PERATURAN MENTERI KESEHATAN NOMOR 736/MENKES/PER/IV/2010 - Octavianti, Bella; Firdaus, Emilda; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The development of refill drinking water depots is growing very rapidly can be seen from its existence everywhere. Refill drinking water is very attractive to the public because the price is relatively cheap and easy to obtain. But it is very unfortunate by the public less concerned with the quality of drinking water consumed is what it meets the quality standards that have been set in accordance with the number 492 / MENKES / PER / IV / 2010 on Water Quality Requirements. The purpose of writing this thesis, namely; Firstly, to know the form of supervision of Pekanbaru City Health Office on drinking water quality of refill drinking water depot, Secondly, To know the obstacle factor from the implementation of supervision of Pekanbaru City Health Office, Third, To know the public policy of future supervision by Pekanbaru City Health Office. This type of research can be classified with the type of sociological juridical research, because in this study the authors directly conduct research on the location or place studied in order to provide a complete and clear picture of the problem under study. This research was conducted at Pekanbaru City Health Office, while population and sample were all parties related to the problem studied in this research, data source used, primary data, secondary data. Data collection techniques in this study with interviews, literature review, and data analysis.From the results of research problems there are two main things that canbe concluded. First, the productivity of Pekanbaru City Health Office in supervising the quality of drinking water to the business of drinking water refill depot can be said not yet successful. This is the existence of the targets that have been set Pekanbaru City Health Office has not reached the maximum. Secondly, the lack of socialization between Dinas Kesehatan and business practitioners of refill drinking water depots and the community about drinking water drinking society is regulated in Kepmenkes. 492 / MENKES / PER / IV / 2010. Suggestion Writer, First, In order to increase the productivity of Pekanbaru City Health Office to be able to identify the refill drinking water depot that has not been checked the water quality by way of water test in the laboratory provided by the Health Department, Secondly, To improve and add employees in conducting quality control Drinking water refill drinking water depot, Third, To improve the performance of Pekanbaru City Health Office in supervision of water quality refill drinking water depot, then Pekanbaru Municipal Health Office must provide funds budget support activities on supervision of drinking water refill depor. All this time the container is the entrepreneurs refill drinking water depot.Keywords: Supervision – Sanctions – Drinking Water Depots